Sustainability diet index: a multi-criteria decision analysis proposal for culinary preparations—A case study - Contreras-Núñez, Rodrigo; Espinoza, Andrea; Cáceres, Paola (Frontiers in Nutrition, 2025)
IntroductionThe environmental impact of food production and distribution has driven the need to integrate sustainability into food services. While research has traditionally focused on carbon and water footprints, other key aspects, such as local product consumption, are often overlooked.MethodsTherefore, this study proposes the development of a sustainability diet index to address these gaps, using Multi-Criteria Decision Analysis. Specifically, the analytical hierarchy process prioritizes sustainability criteria, and the Interactive and Multicriteria Decision Making (TODIM) method ranks them. Two sustainable diet indices are proposed to assess which offers better performance. A case study of a university canteen demonstrates the index's applicability by considering starters, main courses, desserts, and menus.ResultsThe results indicate that rankings based on sustainability dimensions provide a broader perspective, highlighting differences among food menus.DiscussionThe index revealed that menus with local and fewer animal-based ingredients score higher in sustainability, underscoring the relevance of environmental and political factors. Future work considers incorporating other cultural traditional food, menu variations, and vegetarian and vegan options.